Nova pravna ureditev materinskega, očetovskega in starševskega dopusta - Kresal, Barbara (Podjetje in delo, 2014)
The new law on parental protection and family benefits, which was passed by the Parliament in April 2014, introduced - besides the new terminology - some changes into the regulation of maternity, paternity and parental leave. The EU Directive 2010/18, which has to be transposed into the internal legal order, entitles men and women workers to an individual right to parental leave in the length of at least four months, which should, in principle, be provided on a non-transferable basis, whereby at least one of the four months has to be non- transferable. This is one of the measures aiming to promote greater gender equality and to encourage a more equal take-up of leave by both parents.
Keywords: child; družinsko pravo; otroci; starševski dopust; starši